1968
DOI: 10.3181/00379727-127-32923
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic Effect of Ouabain in Dogs

Abstract: I t has been reported that ouabain exerts in vitro metabolic effects characterized by an inhibition of spontaneous (1) and epinephrinestimulated glycogenolysis (2,3) and lipolysis (2,4,5). All these in vitro studies were performed with high concentrations of ouabain M ) . The purpose of the present study was to determine if ouabain exerted metabolic effects in intact animals in a dosage much lower than that used in vitro, and if a similar interaction with the metabolic effeot of epinephrine occurred. Assuming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1968
1968
1977
1977

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Triner, Kypson & Nahas (1968) reported that the intravenous infusion of ouabain in a dose of 1 pglmin-' kg-' for 1 h resulted in a significant decrease (30%; P<0*05) of blood glucose concentration in anaesthetized dogs. Loubatieres et al (1968) and Triner et al (1969) subsequently demonstrated that the fall in blood glucose concentration observed during similar ouabain infusions was associated with a significant increase in plasma insulin concentration in the portal vein.…”
Section: Discussionmentioning
confidence: 98%
“…Triner, Kypson & Nahas (1968) reported that the intravenous infusion of ouabain in a dose of 1 pglmin-' kg-' for 1 h resulted in a significant decrease (30%; P<0*05) of blood glucose concentration in anaesthetized dogs. Loubatieres et al (1968) and Triner et al (1969) subsequently demonstrated that the fall in blood glucose concentration observed during similar ouabain infusions was associated with a significant increase in plasma insulin concentration in the portal vein.…”
Section: Discussionmentioning
confidence: 98%
“…In the first series of experiments, the hypoglycemic effect of ouabain in ten dogs was compared to that of ouabain combined with insulin or propranolol following a protocol previously described (12). Each animal served as his own control and was studied twice at a week's interval.…”
Section: Methodsmentioning
confidence: 99%
“…This dose, which corresponds approximately to four times the therapeutic dosage, did not produce any marked electrocardiographic or plasma potassium changes, but caused a significant decrease in glucose and glycerol plasma concentrations. The same dose of ouabain significantly inhibited the lipolytic and glycogenolytic effects of epinephrine (12). The purpose of the present series of experiments was to investigate the mechanism of the hypoglycemic effect of ouabain, i.e., to establish whether it is a direct effect of the drug on glucose metabolism or whether it is mediated through insulin.…”
mentioning
confidence: 99%
See 1 more Smart Citation